X^2 = 9x + 6
x^2 - 9x - 6 = 0
use quadratic formula : (-b (+-) sqrt b^2 - 4ac) / (2a)
a = 1, b = -9, c = -6
now we sub
x = (-(-9) (+-) sqrt -9^2 - 4(1)(-6)) / 2(1)
x = 9 (+-) sqrt 81 + 24)/2
x = 9 (+-) sqrt 105) / 2
x = 9/2 + 1/2 sqrt 105 or x = 9/2 - 1/2 sqrt 105
Answer:
36.6 cm
Step-by-step explanation:
Each side, starting with the one all the way to the left and going anticlockwise.
7 + 4.3 + 7 + 4.3 + 7 + (7 - 4.3 = 2.7) + 4.3 = 36.6
Answer:
ummmm okay but why tho lol
Answer: y = x^2 - 2 does not represent a linear function because the squared exponent above the variable makes that equation quadratic. Quadratic equations look like parabolas on a graph, rather than lines.
The longest worm is 3/4 as long as the shortest worm.